Caribbean Children's Literature - Nies, Betsy; García Vega, Melissa (Children's Literature Association series, 2023)
"Caribbean Children's Literature, Volume 2: Critical Approaches offers analyses of the works of writers of the Anglophone Caribbean and its diaspora—or, except for one chapter on Francophone Caribbean children’s literature, those who write in English. The volume addresses the four language regions, early children’s literature of conquest—in particular, the US colonization of Puerto Rico—and the fine line between children’s and adult literature. It explores multiple young adult genres, probing the nuances and difficulties of historical fiction and the anticolonial impulses of contemporary speculative fiction. Additionally, the volume offers an overview of the literature of disaster and recovery, significant for readers living in a region besieged by earthquakes, hurricanes, and flooding. In this anthology and its companion anthology, international and regional scholars provide coverage of both areas, offering in-depth explorations of picture books, middle-grade, and young adult stories. The volumes examine the literary histories of both children’s and young adult literature according to language region, its use (or lack thereof) in schools, and its place in the field of publishing. Taken together, the essays expand our understanding of Caribbean literature for young people"-- back cover